The Nrf2 Pathway in Liver Diseases - Zhou, Jiaming; Zheng, Qiuxian; Chen, Zhi (Frontiers in Cell and Developmental Biology, 2022)
Oxidative stress is the leading cause of most liver diseases, such as drug-induced liver injury, viral hepatitis, and alcoholic hepatitis caused by drugs, viruses, and ethanol. The Kelch-like ECH-associated protein 1-NFE2-related factor 2 (Keap1-Nrf2) system is a critical defense mechanism of cells and organisms in response to oxidative stress. Accelerating studies have clarified that the Keap1-Nrf2 axis are involved in the prevention and attenuation of liver injury. Nrf2 up-regulation could alleviate drug-induced liver injury in mice. Moreover, many natural Nrf2 activators can regulate lipid metabolism and oxidative stress of liver cells to alleviate fatty liver disease in mice. In virus hepatitis, the increased Nrf2 can inhibit hepatitis C viral replication by up-regulating hemeoxygenase-1. In autoimmune liver diseases, the increased Nrf2 is essential for mice to resist liver injury. In liver cirrhosis, the enhanced Nrf2 reduces the activation of hepatic stellate cells by reducing ROS levels to prevent liver fibrosis. Nrf2 plays a dual function in liver cancer progression. At present, a Nrf2 agonist has received clinical approval. Therefore, activating the Nrf2 pathway to induce the expression of cytoprotective genes is a potential option for treating liver diseases. In this review, we comprehensively summarized the relationships between oxidative stress and liver injury, and the critical role of the Nrf2 pathway in multiple liver diseases.